Effects of Trichinella spiralis and Echinococcus multilocularis extracts after single and multiple injections on mitosis and hematological and biochemical parameters of mice - T. S. Novik; E. I. Koveshnikova; S. I. Chukina; L. A. Napisanova; O. N. Andreyanov; I. A. Arkhipov; K. G. Kurochkina (Российский паразитологический журнал, 2023)
The purpose of the research is to study effects of Trichinella spiralis and Echinococcus multilocularis extracts on mitosis in a bone marrow cell population, and on hematological and biochemical blood parameters of mice after single and multiple intraperitoneal injections.Materials and methods. The experiment was conducted on outbred male mice. The T. spiralis and E. multilocularis extracts were administered intraperitoneally once or multiple times daily for 10 days at a dose of 80 μg/mouse. Bone marrow cell isolation, microscopic preparations, mitotic index and individual stage determination were made as described in the literature (Ford C. E., Hamerton J. L., 1956). The mouse main peripheral blood parameters were determined with a MicroCC-20 Plus hematological analyzer, and the leucogram was determined by a conventional method. Biochemical blood parameters of the mice were determined with a Clima MC-15 analyzer.Results and discussion. The T. spiralis and E. multilocularis extracts after a single intraperitoneal injection at a dose of 80 μg/ mouse had a pronounced negative effect on the mouse bone marrow cell mitosis with the cell division terminated in the metaphase and a decreased proportion of other mitosis stages. Characteristics were detected of the effects made by the T. spiralis and E. multilocularis extracts on the mouse bone marrow cell mitosis after multiple administration for 10 days. In the reinjection mode of the test extracts to the mice, hematological and biochemical parameters did not change.